1982
DOI: 10.1007/bf01416068
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy of molecular ions: Laser induced predissociation of O 2 +

Abstract: The technique of laser induced predissociation and laser induced fluorescence is applied to study spectra of gas-phase molecular ions. The main feature of the experiment is a beam of mass selected molecular ions illuminated by a pulsed dye laser. Over an extended range of excitation energies spectroscopic information can be obtained about positive and negative ions including transient species.As a first result we present predissociation spectra of 03, b 4Z~ -a4//, A v = 3 and A v = 2 which can well be simulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…However, with the experimentally verified molecular potentials we have identified a strong predissociation channel between the first excited 1 Σ and A 1 Π states, which we are now investigating. It is expected that the rovibrational resolution afforded by predissociation spectroscopy will allow us to efficiently measure molecular ion rovibrational temperatures [26], a crucial step in the demonstration of the method proposed in Ref. [6].…”
mentioning
confidence: 99%
“…However, with the experimentally verified molecular potentials we have identified a strong predissociation channel between the first excited 1 Σ and A 1 Π states, which we are now investigating. It is expected that the rovibrational resolution afforded by predissociation spectroscopy will allow us to efficiently measure molecular ion rovibrational temperatures [26], a crucial step in the demonstration of the method proposed in Ref. [6].…”
mentioning
confidence: 99%
“…2 are summarized in Table I. For comparison, also listed in Table I are the observed peak positions in laser-induced photofragment study by Frey and co-workers, 17 which is the only laser excitation experiment in the present energy range. Totally 47 vibronic bands related to 24 vibrational levels of the A 2 ⌺ ϩ state were identified in the present work, most of which were observed for the first time.…”
Section: Figmentioning
confidence: 97%
“…The N 2 O ϩ molecular ion plays an important role in the ionosphere as it is the intermediate in the reaction of O ϩ and N 2 , 1,2 and thus has been investigated by a lot of experimental techniques, such as fluorescence emission spectrum, [3][4][5][6][7][8][9][10] fast ion beam laser spectroscopy ͑FIBLAS͒, [11][12][13][14][15][16] laser induced fragment, 17 and photoelectron spectroscopy. 18 -20 Extensive studies have been performed to the electronic ground-state X 2 ⌸, and have revealed many complex spectroscopic features arising from various interactions, such as the spin-orbit splitting, Renner-Teller interactions, and the Fermi-resonance couplings in the X 2 ⌸ state.…”
Section: Introductionmentioning
confidence: 99%